2008
DOI: 10.1016/j.bbmt.2008.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Outcome of Allogeneic Hematopoietic Stem Cell Transplantation Using a Conditioning Regimen with Medium-Dose VP-16, Cyclophosphamide and Total-Body Irradiation for Adult Patients with Acute Lymphoblastic Leukemia

Abstract: We retrospectively evaluated the outcomes of 37 adult patients with acute lymphoblastic leukemia (ALL) undergoing allogeneic hematopoietic stem cell transplantation (allo-SCT) conditioned with medium-dose VP-16 (VP, 30 mg/kg), cyclophosphamide (CY, 120 mg/kg), and fractionated total-body irradiation (TBI, 12 Gy) (medium-dose VP/CY/TBI). The median age of the patients was 26 years. Thirteen patients underwent transplantation from HLA-matched related donors (MRD), 18 patients underwent transplantation from HLA-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 30 publications
6
42
0
Order By: Relevance
“…Bone marrow blasts were reduced as expected by DNR/VCR/PSL, so that the leukemia burden could be minimized at allo-HSCT. Administration of DNR/VCR/PSL did not apparently increase the number of severe toxicities, as compared with our previous study [1]. The high CR rates, tolerable toxicities and long-term survival rates in our study are encouraging compared with results of previous studies.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Bone marrow blasts were reduced as expected by DNR/VCR/PSL, so that the leukemia burden could be minimized at allo-HSCT. Administration of DNR/VCR/PSL did not apparently increase the number of severe toxicities, as compared with our previous study [1]. The high CR rates, tolerable toxicities and long-term survival rates in our study are encouraging compared with results of previous studies.…”
Section: Discussionsupporting
confidence: 79%
“…We previously reported that allogeneic hematopoietic stem cell transplantation (allo-HSCT) using a conditioning regimen with medium-dose etoposide, cyclophosphamide, and total body irradiation (VP/CY/TBI) was therapeutically promising for treating acute lymphoblastic leukemia (ALL) [1]. In that study, the 3-year overall survival rate was 88.6% when the patients underwent allo-HSCT in complete remission (CR).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…[6][7][8] The search for alternative regimens to the standard BUCY2 aimed at reducing the relapse rate and also TRM has proven to be difficult. [9][10][11][12] Idarubicin (IDA, 4-demethoxydaunorubicin) was first introduced as a new anthracycline and now it has been widely used to treat AML or relapsed/refractory ALL because it is more effective in multidrug-resistant cell lines and has relatively low cardiotoxicity, but a high penetration rate to central nervous system, compared with DNR or doxorubicin. 13,14 Furthermore, IDA induced a response rate as high as 43% in patients with relapsed or refractory intermediate-high-grade non-Hodgkin's lymphoma, with more than 10 months median duration of response.…”
Section: Introductionmentioning
confidence: 99%
“…However, intensification of conditioning therapy before allogeneic HSCT could still be a viable approach to improve outcome, especially in young adults suffering from high-risk ALL. The composition of the intensified conditioning regimens has been rather conservative in the past, adhering basically to the standard of cyclophosphamide/TBI with the additional use of VP-16 or Ara-C. 17,[31][32][33][34] Here, we report on the first 15 patients with high-risk or refractory ALL who received allogeneic matched unrelated donor or matched sibling donor HSCT after myeloablative conditioning using a novel and more intensive conditioning regimen called FLAMSA-ATG-TBI. Our primary purpose was to evaluate practicability, safety and complication profile of this regimen as a myeloablative conditioning therapy.…”
Section: Discussionmentioning
confidence: 99%